2014
DOI: 10.1016/j.cortex.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of response inhibition circuits in prodromal Huntington disease

Abstract: Cognitive changes in the prodromal phase of Huntington disease (prHD) are found in multiple domains, yet their neural bases are not well understood. One component process that supports cognition is inhibitory control. In the present fMRI study, we examined brain circuits involved in response inhibition in 65 prHD participants and 36 gene-negative (NEG) controls using the stop signal task (SST). PrHD participants were subdivided into three groups (LOW, MEDIUM, HIGH) based on their CAG-Age Product (CAP) score, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 66 publications
(105 reference statements)
1
39
4
Order By: Relevance
“…Atrophy of the ACC has been documented at the early manifest and even premanifest stage [Hobbs et al, 2011]. Functional abnormalities of the ACC in preHD have been related to cognitive deficits, that is, response inhibition [Rao et al, 2014]. Functional abnormalities of the ACC in preHD have been related to cognitive deficits, that is, response inhibition [Rao et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Atrophy of the ACC has been documented at the early manifest and even premanifest stage [Hobbs et al, 2011]. Functional abnormalities of the ACC in preHD have been related to cognitive deficits, that is, response inhibition [Rao et al, 2014]. Functional abnormalities of the ACC in preHD have been related to cognitive deficits, that is, response inhibition [Rao et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, working memory is among the first cognitive domains to be affected and dysfunctions are characterized by reduced connectivity in frontostriatal and frontoparietal networks in mHD [Wolf et al, 2008a[Wolf et al, , 2008b, as well as by volume loss in anterior cingulate cortex, parietal lobe, and striatum [Rosas et al, 2008;Tabrizi et al, 2009]. Also, deficits in executive functions, including motor control [Biglan et al, 2009;Kl€ oppel et al, 2009a], cognitive flexibility [Hanes et al, 1995;O'Rourke et al, 2011;Paulsen et al, 1995], and inhibitory control mechanisms [Georgiou- Karistianis et al, 2007Kl€ oppel et al, 2008;Rao et al, 2014], have been confirmed for both pre-HD and mHD and are possibly the result of striatal atrophy, as well as of volume loss in prefrontal regions [Lawrence, 1998;Rosas et al, 2003]. Moreover, impairments in striatum, amygdala, pallidum, and insula [Henley et al, 2012;Thieben et al, 2002], all considered to be part of the limbic loop [Douaud et al, 2006], may account for the deficits in emotion recognition that are observed in pre-HD and mHD [Gray et al, 1997;Henley et al, 2012;Hennenlotter et al, 2004;Milders et al, 2003;Sprengelmeyer et al, 1996Sprengelmeyer et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the BACHD rats’ performance in such tests might also help to determine if the impairment in the delayed alternation test truly concerned a failure to inhibit erroneous responses, as opposed to a failure to realize that the initiated responses would be erroneous. Interestingly, changes in neuronal signaling have been found in HD patients during performance of tests where they had to inhibit ongoing motor responses [47]. In addition, HD patients [48], HD mouse models [49] and BACHD rats [50] have all been found to show impaired performance in other tests of response inhibition.…”
Section: Discussionmentioning
confidence: 99%